Beyond Riel: Bringing Métis Content into the Classroom - Forsythe, Laura (Canadian Journal of Education / Revue canadienne de l'éducation, 2025)
This article examines the under-representation of Métis perspectives in the Canadian education system and the challenges educators face in incorporating authentic Métis knowledge into their classrooms. Despite a growing emphasis on reconciliation and inclusion of Indigenous content in education, there remains a significant lack of resources and curricula specifically addressing Métis histories, experiences, and worldviews. The article highlights the necessity for Métis-specific educational approaches, drawing on the insights of Métis scholars and community voices. It discusses the development and implementation of a post-baccalaureate course, titled “Beyond Riel: Bringing Métis Content into the Classroom,” that aims to equip educators with the knowledge and tools needed to effectively teach Métis history and culture. Ultimately, this work seeks to promote a more nuanced understanding of Métis realities, facilitating meaningful educational experiences that support reconciliation and honour Métis contributions to Canadian history.